Analysis of Propam's Role in Law Enforcement Against Members of the National Police Who Commit Criminal Acts in the Aceh Police - Ori Istiva; Riza Zarzani (Yayasan Multidimensi Kreatif, 2024)
Indonesia constitutional changes have separated the National Police of the Republic of Indonesia (Polri) from the Indonesia National Army (TNI), making the National Police a civilian institution subject to civil law. With the enactment of Law Number 2 of 2002, members of the National Police are now bound by the applicable disciplinary regulations and code of ethics. Law enforcement against members of the National Police who commit violations is carried out through internal mechanisms, including disciplinary hearings and codes of ethics. The Propam Division has an important role in coaching and enforcing discipline, as well as handling reports of violations. This study aims to analyze the role of Propam in law enforcement against members of the National Police involved in criminal acts in the Aceh Police, as well as identify obstacles faced in the enforcement of the code of ethics and discipline. The results of the research are expected to provide a deeper understanding of the effectiveness of the Propam Division in maintaining the professionalism of National Police members and its impact on public trust.